This book is banned - Haldar, Raj (Sourcebooks eXplore, 2023)
This is a book about dinosaurs. No it's not. Dinosaurs are not allowed. Oh. This is now a book about avocados! Sorry. We deleted those too. FINE. This book is about--nope! Forbidden! Maybe you shouldn't even try reading this book...But what could possibly be inside? Discover just what can happen when ideas are erased instead of expressed.